The Accuracy of Lunar Eclipse Calculations in Irsyad al-Murid Book By Ahmad Ghozali Fathulloh - Sukarni; Ahmad Adib Rofiuddin; Muhammad Zainal Mawahib; Fitriyatul Laili (Universitas Islam Negeri Mataram, 2026)
The issue of eclipses relates to how to determine when an eclipse will occur, where it can be observed, and how to perform eclipse prayers. The book Irsyad al-Murid discusses calculation methods for determining the time of a lunar eclipse. In determining lunar eclipses, this book makes more corrections than other books. Although it does not use supporting tables or schedules, Irsyad al-Murid applies contemporary mathematical formulas. This does not reduce its accuracy, because this book is used as a reference in the study of astronomy in Madura, especially at the Lanbulan Sampang Islamic Boarding School, and is also used as a guideline for determining the beginning of the lunar month by the Calculation and Observation Agency of the Ministry of Religious Affairs of the Republic of Indonesia. The purpose of this study is to analyze the method of calculating lunar eclipses in Irsyad al-Murid and to measure its accuracy using NASA data. This is a qualitative study with the primary source being the Irsyâd al-Murîd book and secondary sources in the form of interviews and supporting literature. The analysis was conducted using content analysis and comparative methods to determine the comparison of the calculation results between the book and NASA. The results of the study show that Irsyad al-Murid uses a contemporary calculation method with complex corrections for the positions of the Moon and Earth, referring to Jean Meeus' Astronomical Algorithms. The difference lies in the use of the Hijri year, while Meeus' book uses the Gregorian year. The level of accuracy is very good, with a difference of only about one to two minutes from NASA's results.